2006
DOI: 10.1111/j.1365-2702.2006.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological approaches to chronic pain management: part 1

Abstract: The application of psychological approaches to chronic pain management is reviewed and discussed. The way in which psychological approaches may be integrated specifically into nursing management of chronic pain is discussed in a later paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 69 publications
4
36
1
Order By: Relevance
“…Most other studies have identified that chronic pain is associated with increased prevalence of depression and/or depressive mood; for reference see (16). In contrast to these results, Sullivan et al (36) found no correlation between pain and BDI.…”
Section: Inter-relationships Between Different Types Of Symptomscontrasting
confidence: 46%
See 1 more Smart Citation
“…Most other studies have identified that chronic pain is associated with increased prevalence of depression and/or depressive mood; for reference see (16). In contrast to these results, Sullivan et al (36) found no correlation between pain and BDI.…”
Section: Inter-relationships Between Different Types Of Symptomscontrasting
confidence: 46%
“…A high prevalence of depression is found in individuals with chronic pain and is reported to be associated with higher levels of pain and disability (for references see (16)). Depressed patients appear to be more prone to use passive strategies than non-depressive patients (17).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the data complemented the conclusions of the National Institute of Health's (NIH) panel (1995) and others (Adams et al 2006;Osborne et al 2006) that found strong evidence for the use of cognitive-behavioral techniques, relaxation techniques and hypnosis in reducing and alleviating pain. The reported decrease of intensity and frequency of subjective pain experiences and increase in functional and coping skills in this study coincide with results of other studies of psychological interventions for chronic pain (Caudill 1995;Osborne et al 2006;Roelofs et al 2002;Secor et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…This highlights the fact that more effort must be invested in ''getting it right in the first place'', perhaps starting with better patient selection; the emerging evidence-base on predictors of poor outcome should assist in this respect [1]. In the meantime, the provision of better education regarding the likely outcome of surgery should at least lead to better informed, and hence more satisfied patients [33], whilst pain management based on cognitive-behavioural principles might be considered for those with chronic persistent problems [2].…”
Section: Discussionmentioning
confidence: 99%